A comparative study of generations X, Y, Z in food purchasing behavior: the relationships among customer value, satisfaction, and Ewom - Wahyuningsih; Hanny Nasution; Yulia Hendri Yeni; Ratna Roostika (Cogent Business & Management, 2022)
The COVID-19 pandemic has fundamentally changed many aspects of lives, including business and consumer behaviour. This study investigates Gen-X, Gen-Y, and Gen-Z in their change in food purchasing behaviour during the pandemic. Further, the study examines the relationships among customer value, customer satisfaction, and eWOM across three generations. It is found that (1) Gen-X, Gen-Y, and Gen-Z perceived different value during the pandemic, (2) Gen-X found to be the cohort that is most concerned with safety value in selecting food compared to the other two cohorts, meanwhile Gen-Y is the cohort with the highest concern on information value, (3) customer value has significant impact on satisfaction and eWOM for Gen-X and Gen-Z, however for Gen-Y, customer value impacts satisfaction significantly, surprisingly, it has no impact on eWOM. Managerial implications and future research directions are highlighted in this study.
Keywords: 650; COVID-19; customer satisfaction; customer value; eWOM; generations XYZ